2015
DOI: 10.1088/0004-637x/804/1/68
|View full text |Cite
|
Sign up to set email alerts
|

The Minimum of Solar Cycle 23: As Deep as It Could Be?

Abstract: In this work we introduce a new way of binning sunspot group data with the purpose of better understanding the impact of the solar cycle on sunspot properties and how this defined the characteristics of the extended minimum of cycle 23. Our approach assumes that the statistical properties of sunspots are completely determined by the strength of the underlying large-scale field and have no additional time dependencies. We use the amplitude of the cycle at any given moment (something we refer to as activity leve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 40 publications
(58 reference statements)
1
8
1
2
Order By: Relevance
“…Despite a relatively low amplitude in cycle 23, the asynchronicity in sunspot activity between two hemispheres helped in maintaining a relatively high level of magnetic activity during minimum of cycle 23. Muñoz-Jaramillo et al [2015] have shown that although the minimum of cycle 23 was one of the lowest in recent history, it did not reach the lowest possible limit because the activity in each hemisphere reached minimum at different times. At the end of cycle 23, sunspot activity in the southern hemisphere lasted longer, as compared to the northern hemisphere.…”
Section: Activity At the End Of Cycle 23 And Beginning Of Solar Cycle 24mentioning
confidence: 97%
“…Despite a relatively low amplitude in cycle 23, the asynchronicity in sunspot activity between two hemispheres helped in maintaining a relatively high level of magnetic activity during minimum of cycle 23. Muñoz-Jaramillo et al [2015] have shown that although the minimum of cycle 23 was one of the lowest in recent history, it did not reach the lowest possible limit because the activity in each hemisphere reached minimum at different times. At the end of cycle 23, sunspot activity in the southern hemisphere lasted longer, as compared to the northern hemisphere.…”
Section: Activity At the End Of Cycle 23 And Beginning Of Solar Cycle 24mentioning
confidence: 97%
“…The maximum umbral field strength stayed virtually constant, at least till 2016. An important piece of additional of information is that the minimum of cycle 23 is not the deepest that is possible (Muñoz-Jaramillo et al 2015). The lowest value of the umbral magnetic field as measured with the traditional Fe 1564.8 nm line is 1500 Gauss.…”
Section: Umbral Magnetic Fieldsmentioning
confidence: 99%
“…In order to better visualise the small changes in the distribution of the area of sunspot groups, we plot the logarithmic variation of the area, as suggested by earlier studies (e.g. Petrovay & van Driel-Gesztelyi 1997;Muñoz-Jaramillo et al 2015;Namekata et al 2019). As we specified earlier, in our analysis we neglected all small groups where the total (umbral and penumbral) area at its maximum did not reach 50 MSH.…”
Section: Maximum Area Of Sunspot Groupsmentioning
confidence: 99%